2000
DOI: 10.1530/eje.0.1430285
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of long-form prolactin receptor mRNA during prolactin-induced luteal regression

Abstract: Objective: Prolactin is capable of both trophic and lytic actions in rat corpora lutea. In corpora lutea responding to a trophic prolactin signal, the long form of the prolactin receptor is the dominant form and is upregulated by prolactin. We investigated whether mRNA for the short form of the prolactin receptor was dominant in corpora lutea responding to a lytic prolactin signal, and whether the relative concentrations of the mRNAs for both forms of the prolactin receptor were changed during this response. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
5
4
0
Order By: Relevance
“…Similar data showing a luteolytic effect of PRL in correlation with the degree of differentiation of luteal cells in the rat were described by Gaytan et al (2001). This regulation was dependent on the long form of PRL-R in the rat (Bowen et al 2000). In males, we have shown that mRNAs coding for the long form of PRL-R were expressed in testes, but we lack data to show any variation.…”
Section: Discussionsupporting
confidence: 81%
“…Similar data showing a luteolytic effect of PRL in correlation with the degree of differentiation of luteal cells in the rat were described by Gaytan et al (2001). This regulation was dependent on the long form of PRL-R in the rat (Bowen et al 2000). In males, we have shown that mRNAs coding for the long form of PRL-R were expressed in testes, but we lack data to show any variation.…”
Section: Discussionsupporting
confidence: 81%
“…This is similar to other models of chronic hyperprolactinemia in which there is loss of the normal response of tuberoinfundibular dopaminergic neurons to PRL (39). Indeed, there is evidence that in other tissues PRL regulates its own receptor, with downregulation observed at extremely high concentrations, although there does not appear to be a consistent PRL level at which this downregulation occurs (41)(42)(43). The dichotomous response we observed appeared to occur with preceding serum PRL levels of approximately 500 ng/ml or greater.…”
supporting
confidence: 87%
“…Furthermore, at the time of the preovulatory LH surge, a simultaneous surge in prolactin occurs in many species (Djahanbakhch et al 1984;Arbogast and Ben-Jonathan 1988;Campbell et al 1990;Anderson et al 2001;Skinner and Caraty 2003). In the rat, this preovulatory prolactin surge has been implicated in causing full regression of the preceding corpus luteum (Bowen and Keyes 1999;Bowen et al 2000) but its physiological role remains unknown in other species. It is tempting to speculate that this subpopulation of prolactin expressing gonadotropes may also be responsible to the preovulatory rise in prolactin.…”
Section: Discussionmentioning
confidence: 99%